The transcription factor IID subunit Taf13 is dispensable for TATA binding protein promoter recruitment and RNA polymerase II transcription - Igor Martianov; Stephanie Le Gras; Guillaume Davidson; Irwin Davidson (iScience)
Summary: The multiprotein complex TFIID, comprising the TATA binding protein (TBP) and 13 TBP-associated factors (TAFs), is an essential component of the RNA polymerase II (Pol II) preinitiation complex (PIC). Cryo-electron microscopy studies suggested a critical role of the TAF11-TAF13 heterodimer in TBP promoter deposition upstream of the transcription start site. To investigate this hypothesis, we inactivated the gene encoding Taf13 in mice and embryonic stem cells (ESCs). Taf13-null embryos implant and survive until E6.5, but fail to undergo gastrulation, while Taf13-null ESCs are viable, but fail to form embryoid bodies and differentiate. Taf13 loss had little effect on TFIID integrity and led to only a mild reduction of TBP promoter recruitment, but led to altered PIC formation and globally reduced Pol II recruitment. Thus, the Taf11-Taf13 heterodimer is not essential for TBP/TFIID recruitment, revealing plasticity in the pathways of PIC formation.